A teaching subject composition since 1966 - Harris, Joseph (Joseph D.) (Utah State University Press, 2012)
"Reviewing the last 50 years of the development of writing studies as a discipline through five key ideas, Harris unfolds a set of issues and tensions that continue to shape the teaching of writing today"-- Provided by publisher.